2009
DOI: 10.1016/j.jfms.2009.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of apoptotic keratinocytes in the feline epidermis: A retrospective light-microscopic study of skin-biopsy specimens from 327 cats with normal skin or inflammatory dermatoses

Abstract: A retrospective light-microscopic study was performed on 294 biopsy specimens of haired skin from cats with various feline inflammatory dermatoses and specimens from cats with normal skin. Conditions expected to frequently have apoptotic epidermal keratinocytes (AKs) (including erythema multiforme, systemic lupus erythematosus, thymoma-associated exfoliative dermatitis, solar dermatitis, and viral dermatopathies) were found to have significantly more AKs than other types of inflammatory dermatoses. Nevertheles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Of these cases, 18% had eosinophils in close proximity to the AKs. Vogel et al 9 reported this occurrence, but did not determine the prevalence. The significance of this finding is still unclear but might point toward an eosinophil-initiated apoptosis.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Of these cases, 18% had eosinophils in close proximity to the AKs. Vogel et al 9 reported this occurrence, but did not determine the prevalence. The significance of this finding is still unclear but might point toward an eosinophil-initiated apoptosis.…”
Section: Discussionmentioning
confidence: 93%
“…3,4,7,9e13 A recent light-microscopic study looking at the frequency of AKs in various inflammatory dermatoses of the cat reported that e in dermatoses not expected to have high numbers of AKs e ectoparasitic diseases had a higher number of AKs than other inflammatory dermatoses. 9 When examining these cases further, eosinophils were occasionally seen directly adjacent to AKs in flea-bite hypersensitivity, cheyletiellosis, and mosquito-bite hypersensitivity.…”
Section: Date Accepted: 8 May 2009mentioning
confidence: 93%
See 1 more Smart Citation